(untitled) (Salam International Academic Journal, 2023)
In this concise article, we undertake a comprehensive examination of Afghanistan’s foreign policy priorities in the current geopolitical landscape. Additionally, we provide a succinct proposal for government officials, outlining key focal points for shaping an effective foreign policy agenda. Afghanistan’s foreign policy priorities can be categorized into three main areas: those pertaining to foreign relations objectives, those centered on the establishment of foreign ties, and those concerning constructive engagement by the Islamic Emirate with the international community. First and foremost, we delve into the priorities associated with foreign relations objectives. These priorities hold paramount significance as they set the course for Afghanistan’s foreign policy, delineating the desired direction for these diplomatic relationships. In this article, we outline these priorities as specific points, emphasizing their importance for all political administrations within the country. Subsequently, we address priorities related to the establishment of foreign relations. We identify five key priorities in this domain, which include: fostering unanimous coordination among Islamic Emirate leaders concerning foreign relations; maintaining a delicate balance between Sharia principles and foreign relations decisions; nurturing trust-based relationships rather than relying on mere symbolic gestures; upholding credibility in all diplomatic dealings; and pursuing a policy of balanced or neutral international engagement. Lastly, we elaborate on priorities linked to positive engagement by the Islamic Emirate with other nations. We underscore the significance of the Islamic Emirate’s multifaceted responsibilities in establishing relations and collaborations with other countries. To this end, we emphasize the importance of prioritizing key areas, such as regional connectivity, mutual economic benefits, water-related issues, addressing foreign armed jihadist groups and security concerns, preventing the imposition of international agendas, resolving border disputes, tackling illegal migrations, among other pertinent matters. By giving due attention to these priorities, we can cultivate constructive relationships with a multitude of nations worldwide. It is imperative that these aforementioned priorities are rigorously observed throughout all stages of Afghanistan’s foreign policy endeavors. Complying with these priorities promises to bring much-needed stability to Afghanistan’s international relations in the current complex environment. Conversely, disregarding these priorities will likely consign any aspirations of successful foreign relations to mere wishful thinking and unattainable dreams.